Elastic-Plastic Characteristics of Rocks at the Academic Vernadsky Station, the Western Coast of Antarctic Peninsula - V. A. Korchin; P. A. Burtny; E. E. Karnaukhova; A. S. Nach (Ukrainian Antarctic Journal, 2004)
Unique data on elastic, density properties as well as some features of the mineral composition of rocks of the western Antarctic Peninsula and adjacent isles has been obtained and summarized in the region of Akademic Vernadsky. The collection studied contains three groups of the Mesozoic and early kainozoic rocks: intrusive, volcanic and veinstones, among which granitoids, andesites, basalts, dolerites. The lowest Vp , Vs and σ values are appropriate to intrusive with the minimal values shown by granites and the higher ones by diorites. In general granites are structural damaged. This may be due to the prolonged influence of the specific climatic conditions and ice cover. Diorites appeared to be more stable to these conditions. Among the volcanic formations rocks with rather high values of these parameters occur. Liparites and trachyandesites show minimal density values, tuffs exhibit mean and dacites and andesites high ones. The lode rocks are featured by wide spectrum of velocity parameters and densities. This is due to their diverse mineral composition and structure. It should be also emphasized that the predominant amount of the samples of the studied mineral formations are represented by slightly decrystallized mineral aggregates with insignificant deficiency. The main effect of the distribution of their velocity parameters is caused by a finegrained mineral mass that fills the most part of the rock. The results of the study are compared with those for the rocks from Crimea and Carpathians. The studies of the elastic and density parameters of rocks revealed some regional features of their distribution. All rock groups show a good correlation between the elastic parameters of rocks and their densities.